Penerapan Game Edukasi Educaplay Untuk Meningkatkan Hasil Belajar Bahasa Arab Siswa XI IPA Di MAS Al- Manar Medan - Fadilla, Mutia; Fanreza, Robie (EL-EMIR Institute, 2025)
This study aims to examine the effectiveness of using the Educaplay educational game in improving Arabic language learning outcomes for 11th-grade science students at Mas Al-Manar Medan. Adopting a quantitative approach with a pre-experimental one-group pretest-posttest design, the research involved 25 students selected through a purposive sampling technique. Data were collected through a pretest, posttest, observation sheets, and a student perception questionnaire. Data analysis used a Paired Sample T-Test to compare pretest and posttest scores, as well as descriptive analysis for the observation and perception data. The results show a highly significant increase in students' average scores after the intervention, rising from 40.36 on the pretest to 71.16 on the posttest. This improvement is supported by observation data, which indicates increased active student participation, and questionnaire results, which reveal students' positive perceptions of this learning method. In conclusion, the use of the Educaplay educational game is highly effective in improving Arabic language learning outcomes, motivation, and student participation